2022
DOI: 10.3389/fmed.2022.822190
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Gut Microbial Dysbiosis and Non-alcoholic Fatty Liver Disease: The Central Role of Porphyromonas gingivalis

Abstract: Gut microbiota play many important roles, such as the regulation of immunity and barrier function in the intestine, and are crucial for maintaining homeostasis in living organisms. The disruption in microbiota is called dysbiosis, which has been associated with various chronic inflammatory conditions, food allergies, colorectal cancer, etc. The gut microbiota is also affected by several other factors such as diet, antibiotics and other medications, or bacterial and viral infections. Moreover, there are some re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 198 publications
(246 reference statements)
0
25
0
2
Order By: Relevance
“…We hypothesize that when the balance of the oral microbial community structure is disturbed, this may lead to the development of oral diseases [ 62 ]. Prevotella , Porphyromonas , and Leptotrichia are known as pathogens that cause oral disease [ 63 65 ]. In the UH group, Prevotella melaninogenica , Leptotrichia wadei , and Porphyromonas pasteri were closely linked with other flora, which supports our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that when the balance of the oral microbial community structure is disturbed, this may lead to the development of oral diseases [ 62 ]. Prevotella , Porphyromonas , and Leptotrichia are known as pathogens that cause oral disease [ 63 65 ]. In the UH group, Prevotella melaninogenica , Leptotrichia wadei , and Porphyromonas pasteri were closely linked with other flora, which supports our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Second, metabolite of intestinal bacteria results in fatty degeneration of liver cells, insulin resistance, and hepatic fibrosis ( Ji et al, 2019 ). Third, endotoxemia attributed to the increase in intestinal permeability is related to pathogenesis of NAFLD ( Wang et al, 2022 ). However, the mechanism of the pathology in which the intestinal flora imbalance induced by oral bacteria contributes to NAFLD has been unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism of the pathology in which the intestinal flora imbalance induced by oral bacteria contributes to NAFLD has been unclear. Studies have pointed out that Porphyromonas gingivalis plays a major role in the process via interfering with the metabolic and immune profiles ( Wang et al, 2022 ). It is not clear if DCs also affect the transmission of pathogenic bacteria and their toxic metabolites to the liver through the portal vein.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies showed that the oral administration of P. gingivalis at simulated doses causes gut microbiota dysbiosis and gut permeability impairment, resulting in systemic inflammation in mice ( 80 , 81 ). It was reported that P. gingivalis -induced dysbiosis is related to arthritis ( 65 , 82 ), type 2 diabetes ( 83 ), and non-alcoholic fatty liver disease (NAFLD) ( 84 ).…”
Section: P Gingivalis and Gut Microbiotamentioning
confidence: 99%